Adherence to dietary prescriptions in patients with acute food protein‐induced enterocolitis syndrome - Stefano Miceli Sopo; Dario Sinatti; Giorgio Sodero; Mariannita Gelsomino; Francesco Mastellone (Wiley, 2022)
ABSTRACT Food protein‐induced enterocolitis syndrome (FPIES) is a non‐Immunoglobulin (non‐IgE)‐mediated food allergy. The elimination diet is the only therapy, the culprit food will be reintroduced if tolerance is acquired. However, it is possible that patients do not follow the recommendations given by the healthcare professional. We investigated if our advice to avoid the trigger food in patients with active FPIES and to reintroduce it in the diet in patients who achieved tolerance had been implemented. We interviewed by telephone the parents of children who were diagnosed with acute FPIES. About 23.2% of our patients disregarded our dietary recommendations: 6/42 (14.3%) of patients who passed a tolerance oral food challenge (OFC) did not eat the trigger food, 4/22 (18.2%) of patients who failed OFC ate the trigger food, and 9/18 (50.0%) of patients who did not perform a tolerance OFC ate the trigger food. We have analyzed some possible influencing factors and no difference was found to be statistically significant. Our results are in line with those reported for IgE‐mediated food allergies. As has already been proposed by others, we suggest reassessing food consumption in all patients after a food challenge.